Situação do modelo de transferência de tecnologia da parceria público-privada entre Embrapa e Fundação Meridional - Dalbosco, Milton (2013)
The Brazilian Agricultural Research Corporation (Embrapa) and the Southern Foundation for Agricultural Research Support (Fundação Meridional), signed in the beginning of year 2.000, a Public-Private Partnership (PPP), looking forward to develop strategies for an efficient model of technology transfer, specially in the dissemination of results from the research projects developed with soybean crop. Among the techniques used by this model, which served as communication channels, are items such as ranking, validation, Special Observation Unit (UOE) and Special Field Day (DCE), Annual Technology Transfer Plan (PATT), Expositive Crop Areas, Technical Trainings, Field Days and also Technical and Commercial Meetings (CRTC). Each one of these tools has its limitations, weaknesses, strengths, flexibilities and generate many benefits, but also suffer the influence of brazilian seed market requirements. Another fact mentioned in this study is that the strategies developped and employed by this public-private partnership provide improvements in effectiveness of instruments for technology transfer and so improved technical and economic performance, specially by bringing together the work of researchers, technicians and farmers. The information exchange among the agents involved in this process and the activity interaction, performed in this model, certainly increase agricultural research in Brazil.